2012
DOI: 10.1093/bioinformatics/bts591
|View full text |Cite
|
Sign up to set email alerts
|

SemMedDB: a PubMed-scale repository of biomedical semantic predications

Abstract: kilicogluh@mail.nih.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
258
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(279 citation statements)
references
References 11 publications
0
258
0
Order By: Relevance
“…Besides treatment relations, identifying the cause of a condition or symptom is also of significance from a prevention perspective. Hence causative relations are also included in well known knowledge bases [15, 25] and also used in discovery applications [36, 42]. Thus in this effort our focus will be on predicting both treatment and causative relations.…”
Section: Background: Knowledge Acquisition and Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides treatment relations, identifying the cause of a condition or symptom is also of significance from a prevention perspective. Hence causative relations are also included in well known knowledge bases [15, 25] and also used in discovery applications [36, 42]. Thus in this effort our focus will be on predicting both treatment and causative relations.…”
Section: Background: Knowledge Acquisition and Approachesmentioning
confidence: 99%
“…That is, instead of looking at what a particular sentence conveys, we model the prediction problem at a global level and build models that output probability estimates of whether a pair of entities participates in a particular relation. Our models are trained with graph pattern features over the well-known knowledge graph SemMedDB [15] extracted from biomedical literature by researchers at the National Library of Medicine (NLM) using the rule based SemRep NLP tool [26]. …”
Section: Introductionmentioning
confidence: 99%
“…In terms of SMDB-DP, there are three causes to the errors. First, the medical concepts in SemMedDB corpus are not precisely extracted (75% accuracy [22]), while Wiki-DP does not have this procedure and information loss. Second, through MetaMap, one disease name might be identified with several concepts.…”
Section: Further Analysis Of Diagnosis Predictionmentioning
confidence: 99%
“…However, SemMedDB has its own limitations. Kilicoglu et al [22] reported that NLM's SemRep, the tool used to build SemMedDB, only achieves 75% extraction accuracy. This means that SemMedDB itself contains many noisy extraction results.…”
Section: Introductionmentioning
confidence: 99%
“…A formal knowledge representation, using the Resource Description Framework (RDF) and the Web Ontology Language (OWL), can help better organize and deliver quality health information. In the biomedical domain, there has been several efforts making Semantic Web knowledge bases (KBs), such as BioNELL [3] and SemMedDB [4]. …”
Section: Introductionmentioning
confidence: 99%